Measuring creativity and risk-taking levels in an English language camp - Ismail, Hanita Hanim; Khairuddin, Zurina; Badi, Jamal Ahmed Bashier (Primrose Hall Publishing Group, 2019)
Second language camps are popular among campers for first-hand experiences with language. This study identifies levels of risk-taking among Diploma of Teaching English as Second Language (TESL) students across gender and creativity. Ninety-three students participated in a twelve-day language camp, and by the end of the camp, they were required to perform a sketch, assessing their creativity in language learning. A modified version of DOSPERT (2003) consisting of 40 items including two items on demographic details, were used to analyse the data through SPSS and presented it in the form of frequency, means, and standard deviation. Results showed that these students were not likely to take risks to do high-risk activities. Neither is there any significant difference in taking risks based on gender nor creativity. As such, it is suggested that language camps should conduct activities which help develop students' higher levels of risk-taking and creativity. © 2019, Primrose Hall Publishing Group.